Designing an Interdisciplinary Course in a Makerspace : Towards collaborative creativity for a sustainable society - Berg, Arild; Sandtrø, Tengel Aas; Güler, Evin; Carella, Alfredo; Norvalls, Mali; Thor, Jenny Helene Haugen; Lysebo, Marius (FormAkademisk, 2020)
The study explored how to develop an elective, interdisciplinary course in a makerspace. The study highlighted the potentials and pitfalls in the transitional space between institutionalised and research-based higher education in relation to the free maker movement. The identified success criteria to set up an elective, interdisciplinary course in a makerspace were connected to the following central concepts: problem, practice, product, bodies of knowledge, critique, scientific discourse, methods, earlier knowledge, personal experience and organisational processes. The study showed how the makerspace elective course can contribute positively to student life by strengthening inclusion, a feeling of belonging, study enjoyment and interdisciplinarity skills in a professional setting. These qualities form a value-based conceptual framework for student active learning that can enable creativity and collaboration, which are essential twenty-first-century skills for a more sustainable society.